Os dentes doentes: uma abordagem biocultural na pré-história de Xingó/Canindé de são Francisco/SE - Silva, Alex Teles dos S. (2018)
The diseases and traumatic lesions in the teeth and jaws are the pathologies that are most often observed in the skeleton. The analysis of oral pathology is of utmost importance for the knowledge and the reconstitution of the dietary habits and the livelihood patterns of our ancestors. It allows to remove several information about the history of the growth of an individual since it is recorded in the dental microstructure that once formed does not undergo remodeling (SANTOS. 2000 apud SILVA. 2018). The hypotheses on eating habits, patterns of physical activity, chronic microtraumatism, repeated impacts by the use of tools, among others (Santos and Coimbra 1994) have been proposed through paleopathological studies of bone and dental. Bioarchaeology is dedicated to the study of human remains, usually already skeletal. This study mainly involves the identification of human bones, so as to make an evaluation such as sex, age of death, stature, etc., and to identify skeletal injuries that may be related to diseases and injuries. These observations contribute to a better interpretation and understanding of the life and death of our ancestors from a biocultural perspective. Initially the objective of this article was to analyze the dentarias pathologies of eleven individuals of three occupation of the site Justino (A, B, C), located in Canindé do São Francisco (SE), the same individuals studied had a chronology dated between 1280 AP to 5570 Ap. When analyzing the dental arches in these burials we intend to find pathologies such as hypoplasia, abscesses, abrasion, caries, etc., so that we can understand the diet and way of life of these populations. For this, we searched for bibliographical material on the topics related to paleopathology and the excavation period of the archaeological area of Xingó in order to seek more information to enrich information in this article. The teeth of the jaws and jaws wereanalyzed from male and female adults of the Justino site. In the results it was possible to obtain information such as sex, age, and if they suffered any type of dental disease. Dental paleopathology is a valuable source of information for archeology, essential for any study that seeks to propose social reconstruction through analysis of the structure and health of past communities.